Arginine and ornithine kinetics in severely burned patients: increased rate of arginine disposal - Yong-Ming Yu; Colleen M. Ryan; Leticia Castillo; Xiao-Ming Lu; Louis Beaumier; Ronald G. Tompkins; Vernon R. Young (2001)
Arginine serves multiple roles in the pathophysiological response to burn injury. Our previous studies in burn patients demonstrated a limited net rate of arginine de novo synthesis despite a significantly increased arginine turnover (flux), suggesting that this amino acid is a conditionally indispensable amino acid after major burns. This study used [ 15 N 2 -guanidino-5,5- 2 H 2 ]arginine and [5- 13 C]ornithine as tracers to assess the rate of arginine disposal via its conversion to and subsequent oxidation of ornithine; [5,5- 2 H 2 ]proline and [5,5,5- 2 H 3 ]leucine were also used to assess proline and protein kinetics. Nine severely burned patients were studied during a protein-free fast (“basal” or fast) and total parenteral nutrition (TPN) feedings. Compared with values from healthy volunteers, burn injury significantly increased 1) fluxes of arginine, ornithine, leucine, and proline; 2) arginine-to-ornithine conversion; 3) ornithine oxidation; and 4) arginine oxidation. TPN increased arginine-to-ornithine conversion and proportionally increased irreversible arginine oxidation. The elevated arginine oxidation, with limited net de novo synthesis from its immediate precursors, further implies that arginine is a conditionally indispensable amino acid in severely burned patients receiving TPN.